Study on ultrasonic machining of Al/Si based composite and Al/Cu alloy - Bansal, Puneet (My University, 2013)
This is an attempt to determine performance characteristics in order to facilitate the machining objectives of high accuracy, high efficiency and low cost in ultrasonic vibration cutting. Also this work deals with the optimization of performance characteristics of an ultrasonic machining process. Ultrasonic machining is one of the most widely used non-traditional machining processes for the machining of non-conductive, brittle materials. Unlike other processes, ultrasonic machining does not damage the work surface thermally which contributes to the successful performance of these materials in service. Ultrasonic vibration cutting as a cutting process has been widely used in the precision machining of difficult to cut materials due to an enhanced cutting stability and increased productivity. Ultrasonic machining is a technology driven process used for machining or finishing brittle abrasives or materials. The USM is effective and practical for all brittle materials, including glass, ceramics, carbides, and graphite roughness, micro-structure, surface hardness, material removal rate as output parameters.
Master of Engineering-Production and Industrial Engineering, Dissertation
Keywords: SEM; XRD; Al/Si